Islamic Perspectives on Installment-Based Online Trading of Gold: Ensuring Compliance with Value and Principles - Deva Mauli Diana; Apriantoro, Muhamad Subhi (Global Research Network, 2023)
Technological advancements have significantly influenced various aspects of life, extending their reach into economic activities, particularly within online buying and selling. A noteworthy facet of this evolution is the virtual trade of gold, a practice increasingly prevalent today. However, online gold transactions primarily reflect the nominal value of the metal without involving physical goods for exchange. Notably, these digital gold transactions often employ installment methods. Within Islamic teachings, careful consideration of installment payment methods is essential to prevent the accumulation of profits resembling usury. This study employs qualitative research techniques, primarily drawing upon literature sources such as books, journals, and prior theses. These sources are carefully selected to align with the teachings of Allah SWT, as elucidated in the Quran and Hadith. The research reveals that according to Islamic principles, the installment-based purchase and sale of gold is permissible based on diverse scholarly opinions. Crucially, this allowance is contingent upon gold being regarded as a precious commodity rather than a medium of exchange, such as cash. Furthermore, the monthly installments must maintain the original value of the gold as initially acquired.